Analisis Disiplin Kerja Terhadap Peningkatan Kinerja Pegawai di Kantor Kelurahan Campaka - Istiqomah, Dzakiyah; Kustiwa, Atep (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze how work discipline affects improving employee performance at the Office of Campaka Village. The background of this research is based on preliminary findings that there are still employees who lack discipline, such as late attendance and not attending morning roll call, which has an impact on the quality of services. This research refers to work discipline indicators, namely attendance, obedience, punctuality, and behavior. Using survey and interview approaches, this research aims toidentify the extent to which work discipline affects the performance of employees. This research uses a descriptive qualitative approach, which aims to describe in depth the phenomenon under study through non-numerical data. The object of research is Campaka Village, one of the villages in Andir District, Bandung City. The results of the discussion regarding the influence of work discipline on employee performance at the Campaka Village Office show that work discipline, which includes punctuality, compliance with rules, and responsibility for tasks, plays an important role in improving employee performance. Disciplined employees tend to provide public services that are more fast, orderly, and satisfying. Discipline also creates a conducive atmosphere. and professionalism. However, there are still some employees who are less consistent in maintaining discipline, so further supervision and coaching is needed.